CHARACTERISTICS OF MATHEMATICAL REASONING IN SOLVING MATHEMATICAL PROBLEMS IN TERMS OF THE COGNITIVE STYLE OF THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 3 WAJO - Suaedy, Nurjayanty (Sains Global Institut, 2019)
This research aims at describing characteristics of students mathematical reasoning in solving mathematical problem regarded from cognitive style. Based on data analysis, it can be concluded that (1) The ways of the subject reasoning of visualizer cognitive style are analyzing, synthesizing, analyzing, then generalizing. While the ways of the subject reasoning who are verbalizer cognitive are synthesizing, analyzing, then generalizing. (2) The sub indicators of subject reasoning of  visualizer cognitive style are presenting mathematical statement through picture specifically and obviously, conducting a beginning asumption specifically, explaining the concept relevancy used through picture, giving reason logically in solving problem and using other alternatives with different strategies, rechecking every steps of completion, tending to conclude  the result of completion with picture and tending to conclude generally based on the specific case from mathematical symptom. While the subjects who are verbalizer cognitive are presenting mathematical statement through verbal symbol specifically and obviously, less specific in doing assumption, relating the concept but ordering based on the sequences known and asked with the writing of symbol in modelling the problem, giving the relevant argument to the steps of completion with the same strategies, rechecking every steps of completion, tending to conclude the result of completion with verbal symbol, and tending to conclude generally based on the specific case and mathematical symptom.